Encyclopedia of Psychopharmacology - Stolerman, Ian P.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Psychopharmacology is the study of the effects of psychoactive drugs on the functioning of the central nervous system at all levels of analysis, thus embracing cognition, behaviour, psychological states, neurophysiology, neurochemistry, gene expression and molecular biology. It includes, as an integral part of its domain, the interaction of environmental and genetic factors with psychoactive drug action, their medicinal and social uses, and their abuse. The Encyclopedia of Psychopharmacology provides detailed information on psychopharmacology and its sub-disciplines, such as clinical psychopharmacology, molecular neuropsychopharmacology, behavioural pharmacology in laboratory animals, preclinical psychopharmacology, human experimental psychopharmacology. The wide-ranging entries in the Encyclopedia of Psychopharmacology are written by leading experts. They will provide basic and clinical scientists in academia as well as industry with valuable information about the field of psychopharmacology. Also people in related fields, students, teachers, and interested laypeople will benefit from the important and relevant information on the most recent developments of psychopharmacology. Entries will fall into several main categories: Methods, techniques and target systems (explaining nature of a technique and its uses and limitations) - Drugs and classes of drug (mainly describing effects and mechanisms of action) - Psychiatric states (explaining drugs used to treat them) - Miscellaneous currently interesting topics that do not fall within the above (e.g. cognitive enhancement, regulation and licensing, substance use in religious rituals).
Keywords: Medicine; Toxicology; Biomedicine; Pharmacology/Toxicology.; Molecular Medicine; Biomedicine general